Current Experience in the Use of Digital Educational Resources: Future Primary School Teachers’ Training - Blyznyuk, Oleksandr (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article presents theoretical insight into thorough analyses of the outstanding experience and best practices in using digital educational resources by educators. We attempt to integrate these findings into training students who obtain a Master’s degree in Primary Education. Intensive use of information and communication technologies has proved efficient in preparing a new generation of innovative highly skilled would-be teachers for primary school in recent years. Although Ukrainian practice in this context is significant, however, huge accomplishments of the best world researchers still produce a noticeable impact on education advancement in many countries. The author draws attention to the relevant issue of training future educators in primary school to use digital open educational resources in their professional activities. The best practical experience of eminent Ukrainian and foreign scholars and teachers was analyzed. The suggested digital resources are examined on the field, purpose, and efficiency of their application with primary school children. The article highlights the educational potential of the popular tools for interactive online and offline communication and assessment of learning outcomes; vivid presentation of the educational content; creative thinking and soft skills development in the classroom as well as automated writing evaluation. Frequent challenges and hardships that educators have to deal with while using digital tools in the classroom are singled out and some solutions to the problem are suggested. The author points out the urgent necessity for young educators to gain new knowledge and skills for not only personal growth and self-development but also, for greater opportunities to be competitive in the contemporary labor market.